Mitigating Seasonal Hunger with Microfinance in Bangladesh : How Does a Flexible Programme Compare with the Regular Ones? - Khandker, Shahidur R.; Khalily, M.A. Baqui; Samad, Hussain A. (Taylor and Francis, 2015)
Microfinance institutions, often criticised for inadequately addressing seasonality and hard-core poverty, have begun to introduce innovative programs designed to tackle both the concerns. One such program in Bangladesh is the Programmed Initiatives for Monga Eradication (PRIME). PRIME exclusively targets the ultra-poor, especially in the country’s northwest region, and offers both production and consumption loans with a flexible loan repayment schedule, and other services. This article assesses the effectiveness of PRIME and regular microfinance programs in reducing seasonal hardship. Findings of this article suggest that PRIME is better targeted than regular microfinance programs and also performs better in mitigating seasonal starvation.